Kinerja Pegawai Negeri Sipil dalam Pelayanan Publik Saat Pandemi Covid-19 di Kantor Badan Pengelolaan Keuangan Daerah (BPKD) Kabupaten Sumbawa Barat - Sami’un, Sami’un (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to find out and examine in depth the performance of civil servants in public services during the Covid-19 pandemic. The method used in this study is a qualitative research method. The steps used in data analysis techniques are editing, clarifying data, then drawing conclusions. Service during the pandemic is not the same as before Covid-19. Working from home during the Covid-19 pandemic did not go as expected, because service activities in the office are work that must be completed at the office, not at home.